2021
DOI: 10.1159/000515041
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine-2,3-Dioxygenase Activates Wnt/β-Catenin Inducing Kidney Fibrosis after Acute Kidney Injury

Abstract: <b><i>Introduction:</i></b> As disorder of tryptophan metabolism is common in CKD, the rate-limiting enzyme of tryptophan, indoleamine-2,3-dioxygenase (IDO), has been reported to be involved in CKD, while the accurate mechanism remains unknown. This study was designed to explore correlations between IDO and kidney fibrosis after ischemia-reperfusion injury (IRI). <b><i>Methods:</i></b> Wild-type (WT) mice and IDO knockout (IDO<sup>−/−</sup>) mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Nonetheless, the blood flow blocking time can be increased at the request of the experimenter. However, it should be taken into account that a prolonged blockage of blood flow may lead to a failure to restore blood supply in the future [ 15 , 56 ]. It is also worth avoiding a strong and prolonged mechanical exposure on the vessels even before the catheter implantation into the artery.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the blood flow blocking time can be increased at the request of the experimenter. However, it should be taken into account that a prolonged blockage of blood flow may lead to a failure to restore blood supply in the future [ 15 , 56 ]. It is also worth avoiding a strong and prolonged mechanical exposure on the vessels even before the catheter implantation into the artery.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Wnt/β-catenin signaling works in a combination fashion with TGF-β signaling in the process of fibrosis, and TGF-β signaling can evoke expression of Wnt/β-catenin superfamily members, and vice versa (Guo et al, 2012). Thus, Wnt/β-catenin/GSK signaling is involved in the development of renal fibrosis in acute kidney injury (Pan et al, 2021) and diabetic nephropathy (Chang et al, 2018). In our model of UUO, the pathogenesis of renal fibrosis involves a complex network orchestrated by necroptosis, oxidative stress, inflammation, TGF-β1, and activation of Wnt/catenin signaling (Jiang et al, 2015;Dai et al, 2020;Jin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aberrant activation of Wnt/β-catenin signaling is linked to a wide range of kidney diseases, including acute kidney injury [ 23 ], aging nephropathy [ 24 ], diabetic nephropathy [ 25 ], and UUO [ 26 ]. Moreover, overactivation of Wnt/β-catenin signaling functions reciprocally with TGF-β signaling to facilitate fibrotic processes [ 27 ]. Using in vivo and in vitro studies, we found that inhibition of Wnt/β-catenin with ICG-001 signaling diminished UUO-induced necroinflammation and fibrosis, suppressing expression of Wnt3α/β-catenin/GSK-3β protein in UUO rat kidneys and HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%